Development of 'Smart Egg Puzzle' as An Innovative Learning Media in Introducing Numbers to Early Childhood - Inkasari, Rizka Febrilia; Kharismawati, Indah; Priatiningsih, Selasi (Universitas Pendidikan Mandalika, 2024)
This study aims to develop a ‘smart egg puzzle’ as an innovative learning media to introduce numbers to 5-6-year-old children at TK Lab.School IKIP PGRI Jember. This research method used research and development with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study included validation instruments, response questionnaires, pretests, and posttests. Quantitative data analysis was processed by presenting percentages using the Likert scale as a measurement scale. Expert validation in media and material has been conducted to assess the feasibility of developing the 'smart egg puzzle' learning media. Practicality testing was performed by evaluating practicality questionnaire sheets conducted by teachers. Effectiveness testing was carried out using pretests and posttests, with the first test conducted before using the 'smart egg puzzle' media (pretest) and the second test conducted after using the 'smart egg puzzle' media (posttest). The results of this study indicated that the ‘smart egg puzzle’ was found to be highly valid, with an 88.75% validation rate from media experts and an 83.92% validation rate from material experts. Additionally, practical assessments by teachers indicated that the learning media was very practical, with an average score of 90.38%. The effectiveness of the ‘smart egg puzzle’ was tested with pretests and posttests, showing a significant improvement in students' number recognition skills. Developing the ‘smart egg puzzle’ was effective and met the validity, practicality, and effectiveness criteria, making it a suitable learning tool for students at TK Lab.School IKIP PGRI Jember.